Trends in the development of territorial public self-government in the Russian Federation - O. V. Baykova; M. R. Tolstov; E. О. Gromyko (Вестник университета)
Within the framework of this article, the features of the organisation of territorial public self-government (hereinafter referred to as TPSG) in the Russian Federation (hereinafter referred to as RF, Russia) are analysed. The authors of this work consider the most acute problems, both financial and regulatory, that slow the development of the TPSG.   The purposes of the study are to analyse the negative aspects of the introduction of the TPSG, which prevent it from being implemented in Russia as effectively as possible, and to form recommendations for solving its main problems.   Limited funding, imperfect regulatory framework, and lack of interest of residents in the organisation of the TPSG hinder its development in the RF. The research methods in this work are: classification, systematisation, generalisation, analysis. The analysis is divided into two categories: document analysis and literature analysis. In the scientific study, the authors examine in detail each of the above problems and suggest possible ways to solve them to promote the development of the TPSG in the country. As a result of the study, recommendations have been developed to solve the problems of the TPSG. The recommendations are aimed at both local authorities and the federal level. Directions for the development of the TPSG are proposed, both on the financial and regulatory side of the issue.